Adverse skin reactions during treatment with cetuximab plus radiotherapy: Multidisciplinary approach to minimize radio-chemotherapy interruption. (April 2015) - Ricci, Francesco; Paradisi, Andrea; Silveri, Sara Lanza; Sampogna, Francesca; Miccichè, Francesco; Bonomo, Pier L.; DiNapoli, Nicola; Valentini, Vincenzo; Capizzi, Rodolfo; Guerriero, Cristina
Abstract Background: Antibodies against the epidermal growth factor receptor (EGFR), such as cetuximab, are effective in loco-regional advanced squamous cell carcinoma of the head and neck (SCCHN) in association with radiotherapy. Cutaneous reactions are well known as adverse events during treatment with EGFR inhibitors. Objective: To identify a multidisciplinary approach for mucous-cutaneous toxicity during cetuximab-radiotherapy treatment in order to reduce the risk of an early radio-chemotherapy interruption. Methods: The data of 38 patients with SCCHN receiving cetuximab and radiotherapy were retrospectively analyzed. The control group (n = 15) received the standardized treatments according to the severity of skin reactions with dermatologic visits only for high degrees of toxicity. The experimental group (n = 23) was monitored and daily treated by dermatologists since grade 1 of cutaneous toxicity. The primary end-point of our study was the mean days of antitumor therapy interruption. Results: The mean number of days of antitumor therapy suspension was 12.6 (7.6) in the standard treatment group and 5.0 (6.6) in the experimental group (p = 0.002). This difference was observed for each grade of toxicity. Conclusion: The early interruption of radio-chemotherapy has a negative impact on survival in patients with SCCHN. In our study, a closer dermatological examination and treatment for all degrees of toxicity reduced early interruptions of chemo-radiotherapy.